An Experimental Investigation on the Effect of Curing Method and Aggregate Type on the Concrete - Ali, Shahrukh; Tiwari, Abhishek (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
The concrete binds our every new construction and from its discovery concrete changes the world construction system and speed up to the mark, and so to test the important property like compressive strength of concrete has become so important. And this property of concrete depends on several values and among them some very prescribed are, curing method, water quality and type of aggregate. This study can be done in many ways, with many parameters, but according to further clear objectives are to examine the concrete and studying its effect on compressive and workability of concrete taking as ideal concrete mixed with potable tap water of local area, to justify the compatibility of Accelerated curing method for determining the compressive strength of concrete on above the traditional ( water immersing method ) curing methods, to compare the effect of using crushed quartzite as a coarse aggregate in concrete by partially and fully replacement of black metals ( gravel ), to make the comparative study with these three parameters water quality, curing method and replacement of gravel with crushed quartzite partially and fully. The various tests of compressive strength determination are performed to take the study to the further level